DNA-TYPE RESULTS SWINE FOR MS4R-GENE AND ITS ASSOCIATION WITH PRODUCTIVITY - Volodymyr KOZYR; Viktor KHALAK; Mykhola POVOD (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The peculiarities of growth, development and fattening qualities of young pigs of different genotypes evaluated by the MC4R gene (marker of meat and fattening qualities, their association with productivity were determined). The true difference between animals of different genotypes (GG, AA and AG) is set at live weight at 3 months of age (4.9-5.2 kg), age of achievement live weight 100 kg (GG – Ag, 7.1 days), thickness of the sphinc at 6-7 thoracic vertebrae (GG – AA – 3.7 mm, GG – AG – 2.1 mm), body length and the chest circumference of the shoulder blades at the age of 6 months (AG – GG, 1.3-1.8 cm). According to O. Wangen's index, the GG genotype is an essential advantage in animals. Compared to the peers of the genotype AA and AG, the difference was 44.86-37.73 %.